Embedding Islamic Values in Education: Strategies for Character Building at Madrasah Kulliyatul Mu’allimin Al-Islamiyyah Gontor - Idawati, Khoirotul; Hanifudin, Hanifudin; Al-Rahim, Ahmed H.; Hosna, Rofiatul; Kibtiyah, Asriyana (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
The objective of this study is to identify the strategies employed by Madrasah Kulliyatul Mu’allimin Al-Islamiyyah Pondok Modern Darussalam Gontor Ponorogo in the pursuit of enhanced character education and to analyse the impact of these strategies on students’ attitudes, behaviours and achievements. A qualitative approach with a phenomenological research design was employed to gather data through observation, interviews, and documentation. Triangulation was conducted to ensure the validity of the data. The data were subjected to an integrated analysis using the Miles-Huberman model and Mintzberg’s 5P theory. The findings demonstrate that the madrasah effectively employs a range of strategies, including the integration of Islamic values into daily life, character-based learning models, the development of positive habits, leadership training, and the active involvement of parents and the community. The reinforcement of character education has had a beneficial impact on students, facilitating improvements in discipline, responsibility, social conduct, and both academic and non-academic achievements. Additionally, it has led to notable enhancements in leadership and collaboration abilities. This study emphasises the importance of integrating character education into all aspects of madrasah activities and highlights the value of collaboration between madrasahs, parents, and the community in fostering students with robust and autonomous character traits.